2022
DOI: 10.1007/s11695-022-05950-z
|View full text |Cite
|
Sign up to set email alerts
|

Staple Line Reinforcement During Laparoscopic Sleeve Gastrectomy: Systematic Review and Network Meta-analysis of Randomized Controlled Trials

Abstract: Purpose Staple line reinforcement (SLR) during laparoscopic sleeve gastrectomy (LSG) is controversial. The purpose of this study was to perform a comprehensive evaluation of the most commonly utilized techniques for SLR. Materials and Methods Network meta-analysis of randomized controlled trials (RCTs) to compare no reinforcement (NR), suture oversewing (SR), glue reinforcement (GR), bioabsorbable staple line reinforcement (Gore® Seamguard®) (GoR), and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 64 publications
2
19
1
2
Order By: Relevance
“…In a meta-analysis of randomized controlled trials for bariatric surgery, such as laparoscopic sleeve gastrectomy, suture oversewing seemed to be associated with a reduced risk of postoperative bleeding, staple line leak, and overall complications; however, no differences were found compared with bioabsorbable materials in the staple line [4]. The procedure for sleeve gastrectomy involves a mostly vertical stapled transection of the stomach and removal of the gastric fundus to create a tubular alimentary channel along the lesser curvature; reconstruction was not included.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a meta-analysis of randomized controlled trials for bariatric surgery, such as laparoscopic sleeve gastrectomy, suture oversewing seemed to be associated with a reduced risk of postoperative bleeding, staple line leak, and overall complications; however, no differences were found compared with bioabsorbable materials in the staple line [4]. The procedure for sleeve gastrectomy involves a mostly vertical stapled transection of the stomach and removal of the gastric fundus to create a tubular alimentary channel along the lesser curvature; reconstruction was not included.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, no signi cant differences were observed in postoperative complications, including postoperative bleeding and anastomotic leakage. Previous studies have demonstrated that staple line treatment techniques, such as oversewing or SLR via roo ng or buttressing, have been implemented to mitigate the risk of staple line complications [4,13,14]. Ojima et al reported that no anastomosis-related complications such as anastomotic leakage, anastomotic stricture, and postoperative gastrointestinal bleeding were found in 24 consecutive patients with gastric cancer who underwent a reinforced stapling technique for reconstruction after laparoscopic distal gastrectomy [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Das Risiko der Nachblutung aus der Klammernahtreihe kann durch eine kurzfristige medikamentöse Blutdruckerhöhung (130 – 150 mmHg) vor Beendigung der Operation und gezielte Blutstillung (Titanclips, Naht, Gewebekleber, biodegradable Klammernahtbezüge) signifikant reduziert werden. Auch wenn hierdurch Adhäsionen induziert werden können, gibt es keine Hinweise auf erhöhtes Risiko von Sleeve-Stenosen 14 .…”
Section: Standardoperationen – Wirkprinzipienunclassified
“…Higher incidence of bleeding and leakage occurred at the start of the learning curve of most surgeons, so we think that correct surgical technique with soft handling of tissues plays a great role in decreasing the incidence of complications. Several studies have revealed that SLR reduces the risk of bleeding and leakage, but its efficacy is still controversial [10].…”
Section: Introductionmentioning
confidence: 99%